pengaruh e-book interaktif untuk mengukur representasi matematis pada optik di SMA - Frisma Winda Afifah Panuqih; Edi Istiyono; Jumadi Jumadi (Postgraduate, University of Mataram, 2024)
This study aims to measure the effect of using interactive e-books in enhancing students' mathematical representation skills on optics material in high school. Mathematical representation involves students' ability to use mathematical symbols, graphs, and formulas to solve physics problems, particularly in the concept of optics, which is often considered abstract. The research method used was a quasi-experiment with a pretest-posttest control group design. The sample consisted of two classes: an experimental class using interactive e-books as learning media and a control class using conventional methods. The results showed an improvement in mathematical representation skills in both classes, with the n-gain value of the experimental class being 0.604 and the control class being 0.557, both in the medium category. However, the experimental class demonstrated a more significant improvement compared to the control class, indicating that interactive e-books are more effective in helping students deeply understand optical concepts. The interactive features in the e-book, such as simulations and animations, provided a more engaging learning experience and helped students visualize abstract concepts. In conclusion, the use of interactive e-books has a positive impact on improving students' mathematical representation skills and can be considered an effective alternative learning medium, especially for science subjects that require better visualization and conceptual understanding.